RUMPOS: Pembenah Tanah Alternatif Produk Teknik Konversi Sampah Organik Untuk Meningkatkan Performa Tanaman Budidaya - Wahjuni Hartati; Syahrinudin Syahrinudin; Triyono Sudarmadji; Rahmad Hidayat (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2023)
Various organic wastes from the agricultural industry are abundantly available, easily and cheaply to process into soil conditioner that can be applied to improve SOM content. RUMPOS is an organic soil conditioner produced from organic wastes by conversion techniques to improve the performance of cultivated plants. The aim of the activity is to introduce RUMPOS as an alternative soil conditioner in crop cultivation. Application of RUMPOS soil conditioner in the right way and dosage may give benefits in plant cultivation. This activity is expected to inspire the community on the utilization of organic wastes. One of the options is the conversion into soil conditioner, leading to the establishment of ameliorant manufacturing industry to supply the need for soil quality management East Kalimantan. Organic-based ameliorant application is an effective way to prevent the deterioration of soil quality and excessive use of inorganic fertilizers. This activity was carried out in collaboration with the Kelompok Wanita Tani Mekarsari, Mugirejo Village, Sungai Pinang, Samarinda, East Kalimantan, Indonesia. The method used is counseling consisting of presentation of material followed by planting practices and discussions. The result of this activity is in the form of additional knowledge on RUMPOS soil conditioner and its use in the cultivation of vegetables and spice crops. Most of the participants also felt inspired to carry out organic waste treatment activities independently into soil improvement in crop cultivation on their farmland